Karyotype analysis of five wild Elymus species of Qinghai-Tibet plateau - Zhang, Pan; Yu, Chengqun; Yang, Peizhi; Cao, Shehui; Hu, Tianming (The Indian Journal of Genetics and Plant Breeding, 2016)
The karyotype of five wild Elymus species of Qinghai-Tibet plateau were determined by root tip squash method. The results showed that all of the Elymus species had satellites in five populations and the karyotype formulae in those materials were: DL population, 2n = 6x = 42 = 32m + 10sm, 2B type; DX population, 2n = 4x = 28 = 2M + 26m, 1B type; SN population, 2n = 4x = 28 = 26m + 2sm, 2B type; NQ population, 2n = 4x = 28 = 20m + 8sm, 2A type; RB population, 2n = 6x = 42 = 38m + 4sm, 1A type. Chromosome variation and degrees of evolution of these five species was DL, SN, NA, DX and RB from high to low level. This study will improve the understanding of the genetic diversity of Elymus of Qinghai-Tibet Plateau and provide effective evidence on genetic relationship and crop breeding.